School Policy Innovation to Reduce Bullying Effect - Riana Nurhayati; Siti Irene Astuti Dwiningrum; Ariefa Efianingrum (AL-ISHLAH: Jurnal Pendidikan, 2021)
Bullying is an unpleasant act that is still a problem in the school environment. To find out about school policy innovations in an effort to reduce the impact of bullying behavior, this will illustrate the relationship between bullying perpetrators and victims of bullying in SMA as well as school policy innovations to reduce the impact of bullying. This research was conducted in high school students of all levels with the number of respondents 1119 students in Indonesia. Descriptive approach with mixed methods. The sample / respondent was determined by purposive sampling technique. The data used a questionnaire and were analyzed with proportions and conducted FGD and interviews with teachers in SMA. The results of the study concluded that: 1) The value of r-count (Pearson Correlations) of the bullying was 0.186 r-table 0.062 and the r-count value for the bullying victim aspect was 0.139 r-table 0.062, meaning that the relationship between the two variables was positive and increased the bullying and victims of bullying, there will also be increased assistance and support from parents, teachers and friends; 2) The solution to reduce bullying effects must implement policies at the macro, meso and micro levels that work systemically and in synergy by creating creative and innovative programs. With the existence of an effective and innovative school policy, bullying cases that occur in schools can be minimized in terms of quality and quantity.